Financing the circular bioeconomy: a win-win for climate mitigation and adaptation - Bodach, Susanne; Somorin, Tosin; Drechsel, Pay; Taron, Avinandan (International Water Management Institute, 2024)
Climate change and resource scarcity pose critical global challenges that demand innovative solutions. Circular bioeconomy provides a transformative framework for mitigating greenhouse gas emissions while enhancing climate adaptation. By applying circular principles, biowaste and wastewater are converted into valuable resources, reducing emissions across sectors such as agriculture and energy, while promoting sustainable practices such as nutrient recovery, biogas generation and safe wastewater reuse. These approaches address water scarcity, reduce reliance on fossil-based inputs, and improve environmental resilience. Financing mechanisms such as international climate funds, carbon credits and climate bonds are pivotal in scaling circular bioeconomy solutions, while enabling policies and capacity building empower stakeholders to drive implementation. The adoption of circular bioeconomy offers a path toward sustainable development, fostering a resilient and resource-efficient future.